UJI TOKSISITAS AKUT DAN SUBKRONIS CAMPURAN EKSTRAK KERING HERBA SAMBILOTO (Andrographis paniculata Nees.) DAN BIJI MAHONI (Swietenia mahagoni Jacq.) - RICKO HARTANTO, 051211131060 (2016)
Andrographis Herbs (Andrographis paniculata Nees.) and Mahogany seeds (Swietenia mahagoni Jacq.) has known as a herbal antidiabetic. Now, combination of Andrographis Herbs (and Mahogany seeds were being developed as a phytopharmacy. The studies was carried out to evaluate acute and subchronic toxicity combination of dried extract from Andrographis herbs and mahogany seeds to fulfill qualification of phytopharmaceutical products registration. Combination of dried extract from Andrographis herbs and mahogany seeds with ratio 2 : 1 were adminestered orally to female mice on acute toxicity and male-female rat on subcronic toxicity. Dose which used for acute toxicity were 16.000, 8.000, 4000, 2.000 and 1.000 mg/kg given once on 24 hour and observed death and toxic symptomps along 14 days. Subchronic toxicity, dose which used were 1.000, 500, and 250 mg/kg BB given everyday along 28 days and observed clinical parameter like hematology, clininical chemistry, and relative vital organ weight and also toxic symptomps The combination of dried extract shows no death and toxic symptomps on all of mice, so that can be determined LD50 of dried exctract are 16.000 mg, which are relatively harmless drug categories. On subchronic toxicity, after did clinical symptomps observation like hematology, clinical chemistry, and relative vital organ weight and analyzed statistically, the results show the combination of andrographis herbs and mahogany seeds dried exctract did not cause toxic effect on male and female rats. Keywords : Andrographis paniculata Nees, Swietenia mahagoni Jacq, Acute Toxicity, Subchronic Toxicity